2020
DOI: 10.3390/ijms21093330
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Release Syndrome in COVID-19 Patients, A New Scenario for an Old Concern: The Fragile Balance between Infections and Autoimmunity

Abstract: On 7 January 2020, researchers isolated and sequenced in China from patients with severe pneumonitis a novel coronavirus, then called SARS-CoV-2, which rapidly spread worldwide, becoming a global health emergency. Typical manifestations consist of flu-like symptoms such as fever, cough, fatigue, and dyspnea. However, in about 20% of patients, the infection progresses to severe interstitial pneumonia and can induce an uncontrolled host-immune response, leading to a life-threatening condition called cytokine rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 113 publications
2
85
1
1
Order By: Relevance
“…Mental health status was measured using the Depression, Anxiety, and Stress Scale (DASS-21), a standardized and validated scale already used in chronic arthritis patients, as well as in previous research related to SARS and COVID-19 [43,44]. The total depression subscale score was divided into normal (0-9), mild depression (10)(11)(12), moderate depression (13)(14)(15)(16)(17)(18)(19)(20), severe depression (21-27), and extremely severe depression (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The total anxiety subscale score was divided into normal (0-6), mild anxiety (7-9), moderate anxiety (10)(11)(12)(13)(14), severe anxiety (15)(16)(17)(18)(19), and extremely severe anxiety .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health status was measured using the Depression, Anxiety, and Stress Scale (DASS-21), a standardized and validated scale already used in chronic arthritis patients, as well as in previous research related to SARS and COVID-19 [43,44]. The total depression subscale score was divided into normal (0-9), mild depression (10)(11)(12), moderate depression (13)(14)(15)(16)(17)(18)(19)(20), severe depression (21-27), and extremely severe depression (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The total anxiety subscale score was divided into normal (0-6), mild anxiety (7-9), moderate anxiety (10)(11)(12)(13)(14), severe anxiety (15)(16)(17)(18)(19), and extremely severe anxiety .…”
Section: Methodsmentioning
confidence: 99%
“…The total anxiety subscale score was divided into normal (0-6), mild anxiety (7-9), moderate anxiety (10)(11)(12)(13)(14), severe anxiety (15)(16)(17)(18)(19), and extremely severe anxiety . The total stress subscale score was divided into normal (0-10), mild stress (11-18), moderate stress (19)(20)(21)(22)(23)(24)(25)(26), severe stress (27)(28)(29)(30)(31)(32)(33)(34), and extremely severe stress (35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Methodsmentioning
confidence: 99%
“…An approved therapy for patients with COVID-19 has yet to emerge; however, there are some medications used in the treatment of SARS-CoV-2 infection globally. They include hydroxychloroquine/chloroquine, which has immunomodulatory effects and can inhibit viral fusion; lopinavir/ritonavir, which is an antiretroviral agent and can block virus replication; dexamethasone as an anti-inflammatory agent; remdesivir, which is an inhibitor of RNA synthesis; and lastly passive immunotherapeutic agents such as tocilizumab, sarilumab, canakinumab, and anakinra [ 6 ]. Although not yet approved by any regulatory agencies, remdesivir has shown evidence of shortened time to recovery among patients with COVID-19 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 infections, it has been reported that cytokine profiles confirm the increased levels of interleukin-1β (IL-1β), IL-2, IL-6, IL-8, tumour necrosis factor-α or TNF-α and some chemokines. 19,20 These elevated levels of cytokines and chemokines confirm the sHLH syndrome in COVID-19 patients. Major clinical manifestations of sHLH include unremitting fever, enlarged liver, liver dysfunction, cytopenias, neurologic dysfunction, and multiorgan failure.…”
Section: Introductionmentioning
confidence: 73%